Analysis of the Provincial Municipal Management (2011-2014) in the SG-1 Sector (Core of the Historical Center of Cuzco) - Durand Cáceres, Karen Xiomara (2021)
As stipulated in the Municipalities Organic Law of Peru’s Constitution - Law No. 27972 (Ley Orgánica de Municipalidades), the success of municipal management depends on the adequate and optimal administration of State resources; in this sense, the application of an adequate methodology to measure and evaluate management performance is very useful for obtaining accurate and current information. This article provides a detailed analysis of wealth management measures applied to the Historic Center of Cusco (SG-1) during the 2011-2014, under the management of the Municipality of Cusco. To that end, we developed a qualitative and quantitative methodological framework to analyze and evaluate the variables of wealth management, and we discuss the results of this analysis, as well as the evaluation criteria, in the results section of this paper.